Circulating miR-320b and miR-483-5p levels are associated with COVID-19 in-hospital mortality. (March 2022) - Giuliani, Angelica; Matacchione, Giulia; Ramini, Deborah; Di Rosa, Mirko; Bonfigli, Anna Rita; Sabbatinelli, Jacopo; Monsurrò, Vladia; Recchioni, Rina; Marcheselli, Fiorella; Marchegiani, Francesca; Piacenza, Francesco; Cardelli, Maurizio; et al.
Abstract: The stratification of mortality risk in COVID-19 patients remains extremely challenging for physicians, especially in older patients. Innovative minimally invasive molecular biomarkers are needed to improve the prediction of mortality risk and better customize patient management. In this study, aimed at identifying circulating miRNAs associated with the risk of COVID-19 in-hospital mortality, we analyzed serum samples of 12 COVID-19 patients by small RNA-seq and validated the findings in an independent cohort of 116 COVID-19 patients by qRT-PCR. Thirty-four significantly deregulated miRNAs, 25 downregulated and 9 upregulated in deceased COVID-19 patients compared to survivors, were identified in the discovery cohort. Based on the highest fold-changes and on the highest expression levels, 5 of these 34 miRNAs were selected for the analysis in the validation cohort. MiR-320b and miR-483-5p were confirmed to be significantly hyper-expressed in deceased patients compared to survived ones. Kaplan-Meier and Cox regression models, adjusted for relevant confounders, confirmed that patients with the 20% highest miR-320b and miR-483-5p serum levels had three-fold increased risk to die during in-hospital stay for COVID-19. In conclusion, high levels of circulating miR-320b and miR-483-5p can be useful as minimally invasive biomarkers to stratify older COVID-19 patients with an increased risk of in-hospital mortality. Highlights: Innovative biomarkers to stratify older patients with COVID-19 at high risk of in-hospital death are urgently needed. Thirty-four miRNAs differentially expressed between deceased and surviving COVID-19 patients were identified through small RNA-seq analysis. MiR-320b and miR-483-5p were confirmed to be significantly hyper-expressed in deceased patients compared to surviving ones. Patients with serum miR-320b and miR-483-5p in the upper quintile had three-fold increased risk to die during in-hospital stay for COVID-19.